PENERAPAN MODEL JIGSAW BERBANTUAN MEDIA LEAFLET DAN PPT INTERAKTIF DALAM MENINGKATKAN HASIL BELAJAR SISWA KELAS VIII DI SMP N 6 WEWEWA TIMUR - Murni Ngongo, Yunita; Makaborang, Yohana; Rambu H. Enda, Riwa (Universitas Cokroaminoto Palopo, 2025)
This classroom action research (CAR) was conducted in two cycles at SMP N 6 Wewewa Timur Middle School. The subjects of the study were all students in class VIII, totaling 20 students. The results of the pre-cycle activity analysis showed that the average cognitive learning outcomes were 60.25 with a percentage of 35%; the average value was 64.5, with a percentage of 45%, increasing to 70.25, with a percentage of 75%. The results of the affective student learning analysis in the first cycle showed that students obtained high scores of 66.6% and moderate 33.4%. The results of the second cycle analysis showed an increase in student scores of 83.3% and moderate 16.7%. Based on the results of the analysis of each cycle, it can be concluded that using the Jigsaw cooperative learning model with the help of Interactive Leaflet and Ppt Media can improve student learning outcomes in the cognitive and affective domains.